Future prospects and recent developments of polyvinylidene fluoride (PVDF) piezoelectric polymer; fabrication methods, structure, and electro-mechanical properties - Mohammadpourfazeli, Soha; Arash, Shabnam; Ansari, Afshin; Yang, Shengyuan; Mallick, Kaushik; Bagherzadeh, Roohollah (RSC advances, 2022)
Polyvinylidene fluoride (PVDF) is a favorite polymer with excellent piezoelectric properties due to its mechanical and thermal stability. This article provides an overview of recent developments in the modification of PVDF fibrous structures and prospects for its application with a major focus on energy harvesting devices, sensors and actuator materials, and other types of biomedical engineering and devices. Many sources of energy harvesting are available in the environment, including waste-heated mechanical, wind, and solar energy. While each of these sources can be impactively used to power remote sensors, the structural and biological communities have emphasized scavenging mechanical energy by functional materials, which exhibit piezoelectricity. Piezoelectric materials have received a lot of attention in past decades. Piezoelectric nanogenerators can effectively convert mechanical energy into electrical energy suitable for low-powered electronic devices. Among piezoelectric materials, PVDF and its copolymers have been extensively studied in a diverse range of applications dealing with recent improvements in flexibility, long-term stability, ease of processing, biocompatibility, and piezoelectric generators based on PVDF polymers. This article reviews recent developments in the field of piezoelectricity in PVDF structure, fabrication, and applications, and presents the current state of power harvesting to create completely self-powered devices. In particular, we focus on original approaches and engineering tools to design construction parameters and fabrication techniques in electro-mechanical applications of PVDF. Original approaches and engineering design tools to fabricate devices in piezoelectric PVDF-based energy harvesting and sensor application.